(untitled) (Architecture Image Studies, 2020)
Intersections between cinema and architecture originated when moving images started recording actual buildings and urban environments and, from their inception, they have been accompanied by extended theoretical reflections on authenticity and objectivity of spatial representation. In recent times, disruptive transformations in the modes and techniques of architectural expression introduced by digital production have originated a fundamental rethinking of these questions. Looking at the impact of technology advances on mechanisms of spatial narrative in cinema, this paper explores how the new forms of architectural expression configure elements and contexts that radically challenge the traditional notions of authenticity and objectivity. Although the new forms of visual narration of architecture in cinema are well understood, the way in which they enhance film narrative is not. With the help of relevant philosophical concepts developed by Gilles Deleuze, this study explores this complex architectural phenomenon to shed light on the mechanisms operating behind it by decoding exemplary cases that transcend the conventional limits of spatial individuation. Through a case study on hybrid, complex and multiple speculative spatialities found in the Marvel movie series, this study offers a theoretical frame to understand the emerging architectural typologies and morphologies. By applying assemblage theory to decode these spatialites, this study offers a description of the novel means used in cinema to redefine architectural types and forms by creatively deterritorializing and reterritorializing consolidated ones. Through the engagement with the Deleuzian understanding of the productive capacity of repetition, the new architectural elements are described as assemblages that expand their both material and intangible boundaries, endowing them with narrative forces of differential individuation.